Production Costs and Commodity Budgets for Selected Florida Vegetables - Scott A. Smith; Timothy G. Taylor (EDIS)
The vegetable budgets presented in these reports are intended to reflect production practices that are considered typical for any given crop in a given area. A consensus of opinion among UF/IFAS personnel and various producers in each production area define typical production practices for each crop. Cost estimates resulting from this process should not be considered as representing the average cost of production in a statistical sense, nor should they be considered as necessarily relating to recommended production practices. The intent of these cost budgets is to establish a benchmark within the range of actual costs that could be expected to produce the crop. This is EDIS document FE436, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published November 2003.